Associations of Chronic Burden, Sleep Characteristics, and Metabolic Syndrome in the Coronary Artery Risk Development in Young Adults Study. Issue 6 (14th July 2022) - Johnson, Dayna A.; Knutson, Kristen; Colangelo, Laura A.; Hale, Lauren; Redline, Susan; Carnethon, Mercedes; Kershaw, Kiarri N.
ABSTRACT: Objective: Chronic exposure to stress is associated with metabolic syndrome (MetS), but the mechanism is unclear. We investigated the associations between chronic burden, sleep, and MetS in the Coronary Artery Risk Development in Young Adults Study. Methods: Chronic burden was self-reported (2000–2001) according to experiences with stressors for longer than 6 months. Wrist actigraphy-measured sleep duration and sleep efficiency were collected for 6 days; sleep duration, sleep quality, and daytime sleepiness were self-reported (2003–2004). MetS was measured during the clinic visit, from 2005 to 2006. Multivariable logistic and Cox proportional hazard models were fit to determine the associations of interest. Mediation by sleep was assessed using the product of coefficients approach. Results: Among participants ( n = 606), the average (standard deviation) age was 40 (3.6) years, 58% were female, and 43% were Black. The prevalences of chronic burden, short sleep (≤6 hours), and MetS were 35%, 43% and 20.5%, respectively. High versus low chronic burden was associated with shorter self-reported sleep duration and higher daytime sleepiness. Chronic burden was associated with 1.85 higher odds (95% confidence interval = 1.11–3.09) of MetS. Sleep characteristics were not associated with MetS. There was no evidence that sleep mediated the chronic burden–MetS relation. Conclusion: Burden of chronic stress may be an emerging novel risk factor for both poor sleep and MetS.